Studi Perencanaan dan Pengembangan Universitas Muhammadiyah Bengkulu sebagai Green Kampus - Pretty Maggiesty Rosantika; Geby Fatona; Rizqiyah Safitri Juwito; Renitha Sari; Mariska Pratimi; Anggi Yudha Pratama (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2025)
Muhammadiyah University of Bengkulu (UMB) has great potential to develop into an environmentally friendly and sustainable Green Campus. This study aims to analyze the existing conditions of the campus, identify challenges and opportunities, and formulate appropriate development strategies to create a greener campus. The research methods used include surveys, in-depth interviews, secondary data analysis, and field observations to gain a comprehensive understanding of the current situation. The findings of the study indicate that UMB faces several challenges, including the limited green open space, which only covers 15% of the total campus area, suboptimal waste management, and the low awareness of the academic community regarding environmental sustainability issues. However, there are several opportunities that can be leveraged, such as the utilization of renewable energy technologies, government policies that increasingly support environmentally friendly initiatives, and the potential for collaboration with external partners from both the private sector and government institutions. The proposed development strategy focuses on five main aspects. First, increasing the campus’s green open space to 30% of the total campus area. Second, the implementation of renewable energy, such as the installation of solar panels, to reduce dependence on fossil fuels. Third, waste management based on technology to effectively recycle waste. Fourth, the application of digital-based environmental education to raise awareness among the academic community. Fifth, maximizing student participation in sustainability activities. This strategy aims to reduce carbon footprints, improve resource efficiency, and create a campus ecosystem that supports the Sustainable Development Goals (SDGs).